Tren Inovasi Pembelajaran Matematika 2020-2026 : Sebuah Systematic Literature Review Tentang Peran Guided Inquiry - Rosmayanti, Neneng; Maryati, Iyam (Jurnal Pendidikan Matematika : Judika Education, 2026)
This study aims to examine the development of a guided inquiry-based mathematics e-module and its impact on students' mathematical competence, which includes cognitive aspects such as creative thinking and mathematical communication, as well as affective aspects such as self-confidence. The method used was a Systematic Literature Review (SLR) with the PRISMA protocol, which synthesized 9 relevant articles from the Google Scholar database through the Publish or Perish application in the 2020–2026 period. The results showed that the e-module development predominantly used the ADDIE and 4D models with a high level of validity and practicality. The integration of the guided inquiry model in digital media has been proven to significantly improve students' creative thinking skills through independent exploration and problem-solving processes. In addition, the use of supporting techniques such as mind mapping and the STEM approach strengthens the effectiveness of learning in building student independence and self-confidence. This study concludes that the guided inquiry-based e-module is an innovative solution that is highly relevant to the spirit of the Independent Curriculum to create student-centered and technology-adaptive mathematics learning.   Keywords: Flat Shapes, Guided inquiry, Independent Learning, Interactive Media